Investigating antecedents of intention to use green agri-food delivery apps: merging TPB with trust and electronic word of mouth - Mouloudj, Kamel; Aprile, Maria; Bouarar, Ahmed; Njoku, Anuli; Evans, Marian; Oanh, Le; Asanza, Dachel; Mouloudj, Smail (Sustainability, 2025)
The rapid expansion of digital platforms has significantly influenced consumer purchasing behaviors, particularly in the agri-food sector. Therefore, this paper investigates the key factors driving customers’ intention to use green agri-food delivery apps (GAFDAs) by integrating trust and electronic word of mouth (eWOM) into the Theory of Planned Behavior (TPB) framework. Additionally, this study examines gender as a moderating variable, assessing whether its influence alters the relationships between key determinants and behavioral intention. Data were collected from 252 Algerian consumers, and the proposed model was tested using SmartPLS 4 and SPSS 26.0. The results confirm that attitude, subjective norms, perceived behavioral control (PBC), trust, and eWOM positively and significantly influence the intention to use GAFDAs, with PBC emerging as the strongest predictor. Moreover, gender moderates the effect of trust on behavioral intention, with trust significantly influencing men’s adoption decisions but not those of females. In contrast, subjective norms and PBC are stronger predictors for female consumers. These findings highlight the importance of gender-specific marketing strategies to enhance GAFDA adoption. This study contributes to the literature by extending TPB with trust, eWOM, and gender moderation, offering valuable insights for marketers, policymakers, and app developers promoting sustainable food consumption.
Keywords: Advertising; Artificial intelligence; Business; Computer science; Control (management); Food delivery; Marketing; Psychology; Theory of planned behavior; Word of mouth; dept.pch

Modeling predictors of medication waste reduction intention in Algeria: extending the theory of planned behavior - Mouloudj, Kamel; Njoku, Anuli; Asanza, Dachel Martínez; Bouarar, Ahmed Chemseddine; Evans, Marian A.; Mouloudj, Smail; Bouarar, Achouak (International Journal of Environmental Research and Public Health, 2023)
COVID-19 caused an increase in the demand for medications, which led to an increase in pharmaceutical waste and there is no doubt that this contributes to environmental pollution. Hence, it became necessary to search for how to protect and improve the environment by encouraging the behavior of medication waste reduction. Accordingly, this study aims to investigate the factors affecting intentions to reduce medication waste. Considering this, we develop an extended theory of planned behavior (TPB) framework by incorporating the constructs of moral obligation, environmental awareness, and medication waste risk perception. Using the convenience sampling method and based on a self-administered questionnaire, a total of 225 usable responses were collected in five Algerian cities. The results showed that positive attitudes (β = 0.316, p < 0.001), moral obligation (β = 0.291, p < 0.001), environmental awareness (β = 0.227, p < 0.001), perceived behavior control (PBC) (β = 0.151, p = 0.001), greater perceived risks (β = 0.127, p < 0.001), and subjective norm (β = 0.096, p < 0.05) significantly and positively influence the medication waste minimization intention. Furthermore, our analyses revealed that the extended TPB model explained 73.40% of the intention variance. In conclusion, we have explored the intentions, and there may be a gap between intent and actual behavior. Therefore, we recommend future studies to examine the factors affecting the actual behavior of medication waste reduction and to investigate environmental ethics and religious commitment as predictors of waste reduction intentions.
Keywords: Africa; dept.pch; environmental health; environmental pollution; medication ecotoxicity; medication waste; moral obligation; peer-reviewed; perceived risk; pharmaceutical waste; theory of planned behavior; unused medications

Factors influencing the adoption of digital health apps: an extended technology acceptance model (TAM) - Mouloudj, Kamel; Bouarar, Ahmed Chemseddine; Asanza, Dachel Martínez; Saadaoui, Linda; Mouloudj, Smail; Njoku, Anuli U.; Evans, Marian A.; Bouarar, Achouak (Integrating Digital Health Strategies for Effective Administration, 2023)
Mobile health apps have been widely considered in the healthcare sector as innovative channels to reach patients and their families. Accordingly, the aim of the chapter was to investigate factors that influence the customers' adoption of digital health apps in Algeria. The authors adopted an extende...
Keywords: dept.pch